PELATIHAN INOVATIF TEKNIK MEWARNAI GRADIASI BAGI GURU PAUD DALAM MENDUKUNG PERKEMBANGAN MOTORIK HALUS ANAK - Fatmawati, Nia; Sofia, Ari; Nawangsasi, Devi; Ulpa, Eska Prawisudawati (PT. Jurnal Center Indonesia Publisher, 2025)
This community service program aimed to enhance the knowledge and skills of early childhood education (PAUD) teachers in applying gradient coloring techniques as a strategy to support children's fine motor development. The training was conducted through three main stages: delivery of material on the importance of fine motor stimulation through art activities, participatory discussions, and hands-on practice in gradient coloring techniques. Evaluation was carried out using pre-test and post-test instruments to measure the improvement in participants’ competencies. The results showed a significant increase in understanding and skill levels. The percentage of participants classified as